2006
DOI: 10.1039/b603012b
|View full text |Cite
|
Sign up to set email alerts
|

Precise ruthenium fission product isotopic analysis using dynamic reaction cell inductively coupled plasma mass spectrometry (DRC-ICP-MS)

Abstract: surface environments and is a key contributor to long-term risk. However, as a mono-isotopic fission product, 99 Tc is limited in its use as a signature to differentiate between different waste disposal pathways that could have contributed to sub-surface contamination at these facilities. Ruthenium fission-product isotopes are attractive analogues for the characterization of 99 Tc sources because of their direct similarity to technetium with regard to subsurface mobility, their large fission yields, and low n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…These results were considered preliminary because the focus of Brown et al (2006s) was on method development. However, the ruthenium isotope analyses suggest a relationship between the vadose zone contamination near tank T-106 and the shallow groundwater contamination (Brown et al 2006a). …”
Section: Fission Product Signaturesmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were considered preliminary because the focus of Brown et al (2006s) was on method development. However, the ruthenium isotope analyses suggest a relationship between the vadose zone contamination near tank T-106 and the shallow groundwater contamination (Brown et al 2006a). …”
Section: Fission Product Signaturesmentioning
confidence: 99%
“…This process, however, appears to be suppressed when tank waste contacts Hanford vadose zone sediment. It is typically observed that, in the absence of reduction, the monovalent oxyanions 101,102,104 (Brown et al 2006a) have been used to trace tank waste migration through the vadose zone and serve as indicators of tank waste contamination in groundwater (Dresel et al 2002).…”
Section: Surface Complexation Approach At the Hanford Sitementioning
confidence: 99%
See 1 more Smart Citation
“…However, innovative approaches, such as analyses of certain stable and radioactive isotope concentrations and signatures are now being used. These studies employ advanced analytical techniques and instrumentation to enable better "fingerprinting" of contaminant plumes, making identification of contaminant source terms plausible (Brown et al 2006b, Cantrell et al 2007). While the use of "fingerprinting" at the Hanford Site is still relatively new, it has the potential to provide significant support in defining the current and future risks associated with contamination currently residing in the vadose zone.…”
Section: 2mentioning
confidence: 99%
“…2 Interferences caused by coexisting compounds in samples can be avoided by sample pretreatment in which the interfering compounds are removed by, for example, coprecipitation or ion-exchange. [3][4][5] Uses of a desolvation apparatus for sample introduction, of a low-temperature plasma, and a high-resolution mass spectrometer are effective ways of reducing and removing interferences. [6][7][8][9][10][11] In recent years, methods employing collision/reaction gas cells using He, H2, NH3, CH4, or O2 have been introduced into ICP-MS to remove the interferences of coexisting ions.…”
Section: Introductionmentioning
confidence: 99%